Review on the barcode technology of android application development for GST products database system - Zainal, Fathiah; Hashim, Nik Mohd Zarifie; A Aziz, Khairul Azha; Mohamad, Najmiah Radiah; Salleh, Azahari; Ja'afar, Abd Shukur (IJARET, 2015)
Starting from 1 April 2015, the Goods and Service Tax will be introduced by the Malaysia Government to be implemented in the country. Since there is no such application provided in the market that can help the struggling citizen to recognize the GST goods, hence; this study will compare the existing Goods and Service Tax system and expose the user an idea to know the items with GST. Selected review papers had been chosen as the man reference to review this specific issue that related to Goods and Service Tax. Advantages and disadvantages of the review paper will be tabulated as to compare and to be used in order to produce a user friendly Android application in the future. In conclusion, the grayscale technique was the suitable and convenient to be used in the image processing. Since, the accuracy of the technique is quite high and from all proposed techniques it is the easy one. The emphasis of the 1D barcodes is about the identification, since the scanning of the barcodes (from the android program) going to be connected to the database; this technique will be make the application to be simple and suitable for all type of user. Keywords: 1D Barcode, Android, Barcode, Database, Goods and Service Tax.